2013
DOI: 10.1155/2013/598163
|View full text |Cite
|
Sign up to set email alerts
|

Transgene Pyramiding of theHVA1andmtlDin T3 Maize (Zea maysL.) Plants Confers Drought and Salt Tolerance, along with an Increase in Crop Biomass

Abstract: The pBY520 containing the Hordeum vulgare HVA1 regulated by the rice actin promoter (Act1 5 ) or the JS101 containing the bacterial mannitol-1-phosphate dehydrogenase (mtlD) also regulated by rice Act1 5 and a combination of these two plasmids were transferred into the maize genome, and their stable expressions were confirmed through fourth generations. Plants transcribing a combination of the HVA1+mtlD showed higher leaf relative water content (RWC) and greater plant survival as compared with their single tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 55 publications
3
22
0
1
Order By: Relevance
“…An increase in the mannitol content was recorded in T lines until 2 dS m -1 salinity levels, which decreased thereafter (3 dS m -1 ). Similarly, a wide range of mannitol accumulation (lmol g -1 FW) was reported for other transgenic plants, such as Arabidopsis (0.05-12; Thomas et al 1995), wheat (0.6-2.0; Abebe et al 2003), and maize (0.26-0.56;Nguyen et al 2013). This clearly indicated that even a very low concentration of mannitol can function in maintaining the osmotic adjustments and also improves the osmotic stress tolerance through scavenging of hydroxyl radicals and stabilization of macromolecular structures (Rahnama et al 2011;Bhauso et al 2014a).…”
Section: Accumulation Of Mannitol and Other Soluble Sugarsmentioning
confidence: 52%
See 3 more Smart Citations
“…An increase in the mannitol content was recorded in T lines until 2 dS m -1 salinity levels, which decreased thereafter (3 dS m -1 ). Similarly, a wide range of mannitol accumulation (lmol g -1 FW) was reported for other transgenic plants, such as Arabidopsis (0.05-12; Thomas et al 1995), wheat (0.6-2.0; Abebe et al 2003), and maize (0.26-0.56;Nguyen et al 2013). This clearly indicated that even a very low concentration of mannitol can function in maintaining the osmotic adjustments and also improves the osmotic stress tolerance through scavenging of hydroxyl radicals and stabilization of macromolecular structures (Rahnama et al 2011;Bhauso et al 2014a).…”
Section: Accumulation Of Mannitol and Other Soluble Sugarsmentioning
confidence: 52%
“…As a strategy for imparting salinity tolerance, overexpressing of mtlD gene coding for MTD has been widely used in various crops (Hema et al 2014;Nguyen et al 2013), including peanut in hydroponic system in our lab (Bhauso et al 2014a). In the present investigation, WT plants exhibited almost negligible, while T lines showed notable MTD activities under salinity stress and non-stress conditions, which suggests the expression of transgene in T lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcription factors are involved in many cellular processes, and hence, stress responsive transcription factors are considered good candidates for improving stress adaptation. Improvement in stress tolerance by transgenic approaches using transcription factors has been achieved in field crops such as rice (Karaba et al 2007;Yu et al 2013), maize (Nelson et al 2007;Nguyen et al 2013), wheat (Saad et al 2013), soybean ) and potato (Bouaziz et al 2013).…”
Section: Introductionmentioning
confidence: 99%